Exposição à violência comunitária e os impactos na saúde mental de adolescentes escolares - Sousa, Victor Hugo Ribeiro de (2024)
Exposure to community violence can have significant impacts on the mental health of adolescents. Living in areas of territorial conflict, where violence is prevalent, can increase stress, anxiety and fear among these young people. Additionally, witnessing or being a victim of violence can cause psychological trauma, resulting in symptoms such as nightmares, anxiety, depression, and sleep disturbances. The present study aimed to analyze the impacts on the mental health of school adolescents exposed to community violence in the municipality of Sobral, Ceará. This is a study with a quantitative approach, with a cross-sectional, descriptive design. The research was carried out in schools in the municipal education network in the municipality of Sobral, Ceará, located in the host district, between the months of August 2023 and January 2024. The sample was composed of 304 adolescents, aged between 12 and 18 years of age, male (47.4%), female (50%) and non-binary (2.6%). For data collection, the “things I have seen and heard” questionnaires by Richters and Martinez were used to assess the exposure of adolescents to community violence, and the Self Report Questionnaire (SRQ-20) to assess the development of Common Mental Disorders. The results for the “things I have seen and heard” questionnaire, according to gender, showed that male adolescents are the most exposed to violence, with a prevalence of hearing gunshots (89.5%), seeing gangs/bandits in the neighborhood (72 %) and seeing someone arrested (67.4%). Depending on skin color or race, exposure to different types of violence was prevalent among self-identified black adolescents. For the results of the SRQ-20 questionnaire, by gender, it was found that female adolescents are those at highest risk for developing CMD (72.4%). In relation to skin color or race, self- declared black people are those most at risk for CMD (63.6%). The study shows that two specific populations are vulnerable to mental illness, namely female adolescents and those self- declared as black. Investigating the causes of mental illness in the adolescent population is essential for the elaboration, execution and evaluation of public policies to guarantee rights in different areas, such as health, social assistance and public security.